2014
DOI: 10.1021/jp503560j
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Wave-Packet Quantum Dynamics Study of the Ne + D2+ (v0 = 0–2, j0 = 0) → NeD+ + D Reaction: Including the Coriolis Coupling

Abstract: The dynamics of the Ne + D2(+) (v0 = 0-2, j0 = 0) → NeD(+) + D reaction has been investigated in detail by using an accurate time-dependent wave-packet method on the ground 1(2)A' potential energy surface. Comparisons between the Coriolis coupling results and the centrifugal-sudden ones reveal that Coriolis coupling effect can influence reaction dynamics of the NeD2(+) system. Integral cross sections have been evaluated for the Ne + D2(+) reaction and its isotopic variant Ne + H2(+), and a considerable intermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For the latter three systems, the CS approximations overestimate the integral cross sections over a high‐energy range. Other previous studies of He + NeH + , Ne + normalH2+, Ne + normalD2+, H + HeH + , He + HeH + , H + + LiH, and H + + D 2 also showed that the CS approximations do not work well for these ion–molecule reactions. Therefore, the failure of the CS approximations for the ion–molecule systems, as we showed in this review article, further suggest that the CS approximations should be cautiously used in the quantum dynamics study of the ion–molecule collisions, which has been first revealed by Han and coworkers in their studies of the other ion–molecule collision systems of D + + H 2 , He + normalH2+, H − + D 2 , and D − + H 2 , .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…For the latter three systems, the CS approximations overestimate the integral cross sections over a high‐energy range. Other previous studies of He + NeH + , Ne + normalH2+, Ne + normalD2+, H + HeH + , He + HeH + , H + + LiH, and H + + D 2 also showed that the CS approximations do not work well for these ion–molecule reactions. Therefore, the failure of the CS approximations for the ion–molecule systems, as we showed in this review article, further suggest that the CS approximations should be cautiously used in the quantum dynamics study of the ion–molecule collisions, which has been first revealed by Han and coworkers in their studies of the other ion–molecule collision systems of D + + H 2 , He + normalH2+, H − + D 2 , and D − + H 2 , .…”
Section: Discussionmentioning
confidence: 82%
“…However, in the time‐dependent wave packet study of Bulut and coworkers for the Li + normalH2+ and its isotopic variants, it has been showed that the CS approximation can yield reliable cross section and rate constant for this reaction system. With their wave packet study on the Ne + normalD2+, Zhang and coworkers illustrated that the CS approximation failed in generating integral cross sections especially at high collision energies. Petrongolo and coworkers applied the time‐dependent RWP method to study the H( 2 S) + HeH + reaction from cold to hyperthermal energies.…”
Section: Validities Of the Cs Approximations: Examples And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final work on this reaction was the use of deuterium, the isotope of the hydrogen atom, to investigate isotope effects. This work CC and CS calculations were, total cross sections of Ne + H2 + and Ne + D2 + reactions were investigated by depending on initial vibrational states [9].…”
Section: Introductionmentioning
confidence: 99%